2016
DOI: 10.1016/j.gaitpost.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Balance recovery is compromised and trunk muscle activity is increased in chronic obstructive pulmonary disease

Abstract: Please cite this article as: Smith MD, Chang AT, Hodges PW, Balance recovery is compromised and trunk muscle activity is increased in chronic obstructive pulmonary disease, Gait and Posture (2015), http://dx.doi.org/10.1016/j.gaitpost. 2015.09.004 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 34 publications
(39 reference statements)
3
38
0
Order By: Relevance
“…In support of this hypothesis, recent reports have shown that COPD in advanced stages is associated with an increased history of falls, balance impairment, and lower extremity muscle weakness. [65][66][67][68] Our results highlight that intercostal and intrinsic foot muscle Ca 21 signaling dysregulation occurs in cigarette smoke exposure. Understanding in more detail the pathophysiology of COPD and its effects in different skeletal muscles could help to further our knowledge of the natural history of the disease and to develop targeted treatments aimed to improve the performance of specific muscle groups.…”
Section: Limitations Of the Mouse Model Of Cigarette Smokementioning
confidence: 62%
See 1 more Smart Citation
“…In support of this hypothesis, recent reports have shown that COPD in advanced stages is associated with an increased history of falls, balance impairment, and lower extremity muscle weakness. [65][66][67][68] Our results highlight that intercostal and intrinsic foot muscle Ca 21 signaling dysregulation occurs in cigarette smoke exposure. Understanding in more detail the pathophysiology of COPD and its effects in different skeletal muscles could help to further our knowledge of the natural history of the disease and to develop targeted treatments aimed to improve the performance of specific muscle groups.…”
Section: Limitations Of the Mouse Model Of Cigarette Smokementioning
confidence: 62%
“…We hypothesize that intrinsic foot muscle dysfunction could contribute to the increased susceptibility to falls in individuals with chronic COPD. In support of this hypothesis, recent reports have shown that COPD in advanced stages is associated with an increased history of falls, balance impairment, and lower extremity muscle weakness …”
Section: Discussionmentioning
confidence: 75%
“…Several reports indicated that decreases in the level of physical activity, which affect the prognosis of patients with COPD, can cause reduced balance ability 2729. Compared with healthy individuals, COPD patients take a longer time to correct losses of balance while walking, and they require more trunk muscle activity 30. If patients with COPD fall and injure themselves, they may experience decreased physical functions, and their resulting reluctance to walk may lead to decreased levels of physical activity 31,32…”
Section: Discussionmentioning
confidence: 99%
“…As another point of view, this recruitment pattern of superficial abdominal muscles during breathing with respiratory loads, observed in subjects ''At Risk" for the development of COPD, may impair the postural control. The excessive trunk muscle activity, namely abdominal muscles, in response to increased respiratory demand, can compromise the trunk moments/movements (Smith et al, 2016). Therefore, the reduced contribution of trunk movement to postural control may be the source to balance deficits that were reported in COPD subjects (Janssens et al, 2013;Smith et al, 2010).…”
Section: Future Investigationmentioning
confidence: 99%